Performance studies of Medium Access Control (MAC) protocols for wireless ad hoc networks - Mohamad Faisal Mohamed. (2011)
Ad hoc wireless networks introduce several challenges. For example, stations using such networks are constrained by factors such as collisions, link errors and limited bandwidth. Thus changes are needed at various levels of the protocol stack, but most importantly at the Medium Access Control (MAC) layer, to address these challenges. This report discusses the challenges in the design of wireless MAC protocols and also a survey on the MAC protocols that produce high throughput. The MAC protocol chosen to be coded is the Concurrent Transmission MAC protocol (CTMAC). As the CTMAC protocol is yet to be fully coded, simulation is thus carried out on the IEEE 802.11 MAC protocol to evaluate its performance with increasing node density. From the simulation results obtained, several conclusions are then drawn.